(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: The present study intended to determine the risk factors of severe exacerbation in chronic obstructive pulmonary disease patients and correlation factors. Material and Method: A descriptive study was conducted at the Binh Dinh Tuberculosis and Lung disease Hospital from March 2022 to September 2023. The clinical and paraclinical relevant data for acute exacerbation (age, sex, Smoking status, BMI, Disease duration , Acute attack per year, co-morbidity, severity of COPD, COPD medication, annual influenza vaccination, compliance with inhaled drug use, chest radiographic abnormality,white blood cells, Neutrophile/ lymphocyte ratio,C reaction Protein, sputum culture) were compared between severe AECOPD and mild- moderate AECOPD patients by logistic regression analysis. Results: Out of 140 AECOPD patients, 112 (80%) had severe AECOPD. The eleven risk factors BMI underweight (OR: 3.92 95% CI 1.59 – 9.66);Smoking > 20 packs-year (OR 3.32 95% CI 1.35- 8.45); Disease duration > 5 years ( OR 23.56 95% CI 7.75 – 71.6); hypertension ( OR 2.75 95% CI 1.04 – 7.31); chronic kidney disease (OR 9.88 95% CI 1.29 – 75.91);improper use of inhaled devices (OR 3.50 95% CI1.68 – 9.23); Influenza non-vaccination (OR 5.47 95% CI2.6- 38.4) white blood cells > 10 Giga/L( OR 9.40 95% CI 3.74 – 23.66); Neutrophil/Lymphocyte ratio >4 (OR 2.58 95% CI 1.09 – 6.10); emphysema ( OR 4.09 95% CI 1.09- 6.10);sputum culture positive ( OR 11.77 95% CI 4.54 – 30.54).There were positive correlation between CRP and white blood cell count, CRP and N/L ratio. Conclusion: Eleven risk factors of severe AECOPD among patients